2015
DOI: 10.1016/j.nefro.2015.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Características clínicas, evolución y pronóstico de la nefropatía membranosa idiopática en función de la presencia de anticuerpos contra el receptor tipo M de la fosfolipasa A2

Abstract: Anti-PLA2R-negative patients with idiopathic membranous nephropathy were older and experienced spontaneous remission more often than anti-PLA2R-positive patients. No differences in terms of treatment response, recurrences, and final prognosis were observed between both groups of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
2
0
3
Order By: Relevance
“…It has been suggested that in the patients with anti-PLA2R antibody-associated PMN, the antibody titer might be used to predict prognosis, supposing that there is a lag between the immunological and clinical response [ 15 ]. Despite the fact that around 30% of patients with PMN are anti-PLA2R-negative, even in their renal tissue, little information is available on these patients [ 16 ]. Most studies using PLA2R to predict prognosis focused on the anti-PLA2R status of the patients, and few considered the glomerular PLA2R antigen [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that in the patients with anti-PLA2R antibody-associated PMN, the antibody titer might be used to predict prognosis, supposing that there is a lag between the immunological and clinical response [ 15 ]. Despite the fact that around 30% of patients with PMN are anti-PLA2R-negative, even in their renal tissue, little information is available on these patients [ 16 ]. Most studies using PLA2R to predict prognosis focused on the anti-PLA2R status of the patients, and few considered the glomerular PLA2R antigen [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of aetiology, MN is most often primary (pMN 80%)—formerly named idiopathic MN—but may be secondary to a variety of conditions, including systemic lupus erythematosus, hepatitis B antigenaemia, malignancy and the use of certain drugs or toxins [1, 5]. It was not until 2009, when antibodies against M-type phospholipase A2 receptor (APLA2R) were discovered, that an underlying cause could be identified to explain the pMN in a great proportion of cases [2–4, 6, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Las características demográficas de los pacientes con NM aparentemente primaria (Tabla 1), revelan predominio de población masculina y edad promedio entre 50 a 60 años, características semejantes a lo descrito en otros trabajos 9,10 .…”
Section: Discussionunclassified
“…Los aspectos clínicos en relación al síndrome nefrótico fueron semejantes en los pacientes con Ac anti-PLA2R positivo y negativo, al igual que lo publicado por Hofstra et al 9 y Escalante et al 10 , salvo la magnitud de la proteinuria que fue claramente mayor en el grupo con Ac anti-PLA2R positivo, no descrito en otras series. La prevalencia del Ac anti-PLA2R sérico en esta serie fue de 53,6% (15/28), semejante aunque en el límite inferior a lo reportado por otros investigadores 10,11,18 . Este hallazgo puede ser explicado porque es una muestra pequeña o porque se trata de una población distinta.…”
Section: Discussionunclassified
See 1 more Smart Citation